Determinan Audit Fee (Studi pada Perusahaan Manufaktur yang terdaftar di BEI Tahun 2018-2020) - Fachriyah, Nurul (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2024)
This study aims to identify the determinants of audit fees in real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2020. Using a quantitative approach and linear regression analysis on secondary data from annual financial reports, it was found that among the four independent variables examined—going concern, corporate governance, company size, and audit firm size—only company size has a significant effect on audit fees. Company size influences audit fees due to greater operational complexity, audit risk, and the need for additional services. These findings support Agency Theory and have practical implications for large company management to manage risk and complexity to control audit costs, as well as for auditors and policymakers to consider company size when setting audit fees and formulating regulations.